TEACHING ENGLISH AS A FOREIGN LANGUAGE - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2021)
This article is about teaching English as a foreign language to students and how it can be taught in a foreign language. It also provides information on the challenges of learning English as a Foreign language.